Iran and the CIA : the fall of Mosaddeq revisited - Bayandor, Darioush, 1939- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2010)
"In the early 1950s, frail septuagenarian prime minister of Iran, Doctor Mohammad Mosaddeq, shook the world by challenging Britain by nationalizing Iran's British-run oil industries. In August of 1953, he was overthrown. Revisiting these events with astonishing new evidence, this book challenges the conventionally-held theory of foul play by the CIA"--Provided by publisher.
The advent of Mosaddeq and the oil crisis -- Mosaddeq's second government, July 1952- August 1953 -- The downslide -- The downfall -- Anatomy of August 19 -- Where did the spark come from?
Includes bibliographical references (p. 234-237) and index.
Keywords: Mosaddeq, Mohammad, -- 1880-1967.; United States. -- Central Intelligence Agency -- History -- 20th century; Petroleum industry and trade -- Political aspects -- Iran -- History -- 20th century; Iran -- History -- Coup d'état, 1953.; Iran -- Politics and government -- 1941-1979.; United States -- Relations -- Iran; Iran -- Relations -- United States